Optimización del proceso de difusión en Redes Metropolitanas. - Amaya Díaz, Vinicio Marcelo (2016)
The rapid progress of technologies that enable a wireless communication and the rapid increase in devices those are suitable to connect to this technology. The MANETs networks have raised considerably the opportunity for research on computer networks, where mobile nodes are able to enter and disappear in random, and this type of configurations should have the ability to be attached to these users. The issues raised and the main investigations followed, to join the current development, are described on the basis of the Evolutionary Algorithms. Then express objectives set out in the present investigation. To finish shows a small summary of how it is organized the same. Used the multi-objective genetic algorithm NSGA-II for information that are expressed the comparative results of the metric hipervolumen, where the best results are achieved with the algorithm followed by PAES and MOLS. According to the implementation of multiple algorithms and taking into consideration the tests carried out with the algorithm NSGA-II, is considered the dissemination to be evaluated by the university authorities.